The Significance of Diagnosing Fractures of the Coronoid Process of the Mandible in the Occurrence of Temporomandibular Joint Dysfunctions - Glushchenko, Т. Л. (Actual Dentistry, 2026)
Summary. The etiological factors of temporomandibular joint disorders are increasingly relevant; over the past decade, the number of publications on this topic has increased significantly. However, until now, the traumatic factor in the development of TMJ disorders has not been sufficiently covered due to complicated analysis and insufficient diagnostics. According to analytical data, mandibular fractures are the most common type of fractures of the facial bones, among which, according to leading scientists, fractures of the coronoid process of the mandible account for 19% to 35%, of which 84% of cases are unilateral fractures, and 16% are bilateral. The goal is to establish the significance of diagnosing fractures of the coronoid process of the mandible as an etiological factor of temporomandibular joint disorders. Materials and methods of the study. Fifty patients aged 12 to 72 years who presented with TMJ pain disorders and had previously undiagnosed and untreated mandibular coronoid fractures were selected. All patients underwent TMJ examination with cone-beam computed tomography or magnetic resonance imaging, followed by palpation (according to the M. Rocobano pain map) and deprogramming of the masticatory muscles (using the Cois or Dawson method). Results. During the study, the following options for visualization of old fractures were identified: 1) ideal adaptation—cases with a high risk of being undiagnosed, characterized by a complete or almost complete absence of the fracture line, determined by the specific shape of the articular head, patient interview data, and only at the initial stages of rehabilitation; requires extraordinarily high-quality diagnostics. 2) Optimal adaptation—the fracture line is well visualized, even after many years, has a restored cortical plate, and destructive changes in the structure of bone tissue are often present. 3) Low adaptation: the fracture line is well visualized, the cortical plate is destroyed, and destructive changes in the structure of bone tissue are present. Conclusions. It has been established that among patients presenting with temporomandibular joint disorders, 15% of patients have an old, undiagnosed injury, which is an etiological factor of TMJ disorders. Their treatment is complicated by the long duration of this pathology’s development. This indicates the need for mandatory diagnostic measures, in particular radiological examinations, in patients even with non-obvious signs of maxillofacial injuries at the initial presentation and in subsequent presentations with signs of TMJ disorders.